A new flavan from the Drynaria bonii H. Christ rhizomes. Issue 7 (2nd April 2016) - Trinh, Pham Thi Nhat; Tri, Mai Dinh; Hien, Dang Chi; An, Nguyen Huu; Minh, Phan Nhat; An, Pham Ngoc; Dung, Le Tien
Abstract : In Vietnam, the medicinal plant Drynaria bonii H. Christ is used for the treatment of osteoporosis, bone fractures, and stimulate the growth of hair, treat tinnitus (Ho 2002; Loi 2004). In this article, experiments were designed to investigate the proliferation activity of ethanol, n -hexane, chloroform, ethyl acetate and methanol extracts from D. bonii rhizomes on MG-63 human osteoblast-like cells. The results showed that methanol and hexane extracts had the ability to proliferate MG-63 cells at the concentration varying from 0.1 to 0.01 μg/mL. In particular, at the concentration of 0.01 μg/mL, hexane and methanol extracts illustrated the highest proliferation ratio with 9.31% and 6.16%, respectively. By column chromatography, a new compound named drynaether A (1 ) and five known compounds uracil (2 ), 4′-hydroxy-7-methoxyflavan (3 ), kaempferol (4 ), indole-3-carboxylic acid (5 ) and protocatechuic acid (6 ) were isolated and identified from the methanol extract. Abstract :